Copper Removal from Aqueous Solutions by Means of Ionic Liquids Containing a ?-Diketone and the Recovery of Metal Complexes by Supercritical Fluid Extraction - Romero-Figueroa, J (John Wiley and Sons Ltd, 2014)
BACKGROUND: This work is focused on the removal of Cu(II) ions from aqueous solutions by means of different hydrophobic imidazolium-based ionic liquids containing 1,1,1-trifluoro-2,4-pentanedione (TFA) as extractant and the subsequent extraction of the metal complexes formed in the IL by means of supercritical fluid extraction. RESULTS: Solutions containing between 250 and 500 mg L-1 of Cu(II) ions were contacted with [bmim][PF6], [hmim][PF6] and [bmim][Tf2N] containing TFA. After liquid-liquid extraction, both phases were analysed, verifying the formation of neutral complex Cu(TFA)2 as the predominant extraction mechanism in [bmim][PF6] and [bmim][Tf2N]. Meanwhile, the extraction of Cu(II) in [bmim][PF6] was strongly influenced by the direct interaction between the metal ion and the IL. ILs used in L-L extractions were regenerated using supercritical CO2 at 18 MPa and 40°C. [bmim][Tf2N] showed the highest accumulative extraction percentage (? 80%) after sequential loads of Cu(II) ions. CONCLUSION: From these tests, [bmim][Tf2N] was the solvent that showed the best performance in terms of accumulative extraction and recycling capacity in sequential extraction cycles mediated by regeneration with supercritical CO2. This study demonstrates that this process could be considered an alternative separation technique for metal ions using green solvents, and with extractant requirements lower than in conventional solvent extraction operations. © 2014 Society of Chemical Industry.